Effect of urea supplementation to urea molasses mineral block (UMMB) lick on nutrient utilization and rumen fermentation pattern in crossbred cattle - TOPPO, SAROJ; MEHRA, U R; DASS, R S (The Indian Journal of Animal Sciences, 2013)
The effect of incremental urea supplementation on intake of urea-molasscs mineral blocks (UMMB), nutrient utilization and rumen ferntentation was investigated on 16 adult crossbred cattle. They were divided into 4 equal groups following u completcly randomized design. Animals were offered wheat straw and UMMB lick ad lib. and crushed maize grains to meet out the energy requirements. In addition to this, animals in groups 1 to 4 were offered urea @ 0, 15,30 and 45 g/ animal a day, respectively, A metabolism trial of 6 days duration was conducted, Results revealed that intake and digestibility of all the nutrients were alike except that CP intake was significantly (P<0.05) more in urea supplemented groups. However, the intake of UMMB was highest in group 2 where urea was supplemented @ 15g/day. Balances ofN linearly increased due to various levcls of urea supplementatioll. A fermentation study was carried out on 4 rumen fistulated adult cattle following 4 x 4 latin-square design. Strained rumen liquor was collected and analyzed for pH, ammonia nitrogen, totalÂ·N, TeA preeipitable-N, rumen fluid volume and rumen fluid flow rate. Total N, ammonia-N and TVF A were significantly affected due to urea supplementation. There was no significant change in various blood biochemical constituents. It can be concluded that 15g urea supplementation is sufficient to maintain the optimum intake of UMMB and fermentation pattern.